The role of voluntary counselling and testing in modifying risky sexual behaviour for HIV infection : cross-sectional study from the ‘Wellness Clinic’ of a District Hospital in rural Limpopo, South Africa - Gonzalez, J. A. Leon (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2016.